Entrainment Mechanism of Viscoplastic Fat Particles and Tribofilm Formation in Soft Contact Tribology. (December 2022) - Lim, Ming Y.; Xu, Yuan; Shewan, Heather M.; Stokes, Jason R.
Abstract: Lubrication of oil-in-water emulsions containing viscoplastic fat particles is studied using soft-contact tribology, a technique that is relevant to the performance and evaluation of foods and personal care products. A decrease in friction in the boundary-mixed regime over sequential tribological runs is attributed to the deposition of fat particles and formation of a fat film on the tribo-surfaces. This is surprising because the particles are larger than the predicted surface separation in this regime. In addition, a fat film is not formed when the system is in the elastohydrodynamic regime despite surface separation being comparable to the particle size. We utilise ellipsometry as a novel approach to quantify the thickness of the fat film and probe how this is influenced by surface deformation. The fat film thickness follows a two-thirds power law scaling with normal load, which is consistent with the predicted indentation depth following Hertzian contact mechanics. The results highlight that surface deformation facilitates entrainment of fat particles in the boundary-mixed regime and fat film formation that governs lubrication properties. Graphical Abstract: Unlabelled Image Highlights: Viscoplastic fat film formation sequentially decreases friction in soft-contact tribology. A fat film forms when system is in the boundary-mixed regime (narrow gap). A fat film is not formed when the system is in the EHL regime (large gap). Film thickness scales with predicted surface deformation from Hertzian contact mechanics.